PSYCHOLOGICAL FEATURES OF CORRECTION OF COMBATANTS ANXIETY USING ART-THERAPY (Psychology Travelogs, 2025)
The article examines the psychological characteristics of anxiety in combatants and the effectiveness of art therapy techniques aimed at its reduction. Anxiety among military personnel is viewed as a complex multilevel phenomenon shaped by exposure to combat stress, traumatic experience, prolonged psycho-emotional tension, chronic stress, threat to life, loss of comrades, prolonged hypervigilance, and physiological overstimulation. The study provides an overview of international and Ukrainian scientific approaches to understanding combat-related anxiety, emphasizing the vulnerability of service members during transition from combat operations to peaceful environments. The study presents empirical data obtained from 100 combatants using the Beck Anxiety Inventory, the Spielberger-Hanin Anxiety Questionnaire, J. Taylor's Anxiety Scale, and the projective technique by J. Buky "House-Tree-Person." The initial assessment revealed predominantly high and moderate levels of anxiety, along with projective indicators of emotional tension, hypervigilance, and signs of traumatic stress. A specially designed art therapy correctional program was implemented, including drawing therapy (isotherapy), collage, mandalas, various body-oriented art practices, and relaxation techniques.  Post-intervention assessments demonstrated a significant decrease in anxiety levels across all applied diagnostic scales and a reduction of projective signs of emotional overload. The results confirm that art therapy serves as an effective psychological tool for restoring emotional stability, enhancing self-regulation, and improving adaptation of combatants. Practical recommendations for psychologists and all mental health professionals working with military populations.
Keywords: anxiety; combatants; art therapy; mental trauma; emotional stability; adaptation; psychocorrection; mental health